Serosurveillance of SARS-CoV-2 in companion animals in Sarawak, Malaysia - Tan, Cheng Siang; Davies Belayong, Bandak; Sultana Parvin, Habeebur-Rahman; Tan, Lee Tung; Andrea Lim, Li Li (Biomed Central, 2023)
SARS-CoV-2 is a zoonotic betacoronavirus that was first reported at the dawn of 2019 in Wuhan, China and has since spread globally, causing an ongoing pandemic. Anthroponotic transmission was reported early, with confirmed infections reported in 26 species to date, including dogs and cats. However, there is a paucity of reports on the transmission of SARS-CoV-2 to companion animals, and thus, we aimed to estimate the seroprevalence of SARS-CoV-2 in dogs and cats in Sarawak, Malaysia. From August 2022 to 2023, we screened plasma samples of 172 companion animals in Sarawak, Malaysia, using a species-independent surrogate virus neutralization test. Our findings revealed the presence of neutralizing antibodies of SARS-CoV-2 in 24.5% (27/110) of dogs and 24.2% (15/62) of cats. To the best of our knowledge, this is the first report of the seroprevalence of SARS-CoV-2 in companion animals in Malaysia. Our findings emphasize the need for pet owners to distance themselves from their pets when unwell, and a strategy must be in place to monitor SARS-CoV-2 in companion animals to assess the potential impact of the virus on companion animals.